Membrane androgen receptor sensitive Na+/H+ exchanger activity in prostate cancer cells. Issue 9 (4th March 2014) - Chatterjee, Soumya; Schmidt, Sebastian; Pouli, Stella; Honisch, Sabina; Alkahtani, Saad; Stournaras, Christos; Lang, Florian
Abstract : Membrane androgen receptors (mAR) are expressed in several tumors. mAR activation by testosterone albumin conjugates (TAC) suppresses tumor growth and migration. mAR signaling involves phosphoinositide‐3‐kinase (PI3K) and Rho‐associated protein kinase (ROCK). PI3K stimulates serum‐ and glucocorticoid‐inducible kinase SGK1, which in turn activates Na + /H + ‐exchangers (NHE). In prostate cancer cells cytosolic pH (pHi ) was determined utilizing 2′, 7′‐bis‐(2‐carboxyethyl)‐5‐(and‐6)‐carboxyfluorescein‐fluorescence and NHE‐activity utilizing Na + ‐dependent cytosolic realkalinization following an ammonium pulse. TAC (100 nM) significantly increased pHi and NHE‐activity, effects abrogated by NHE1‐inhibitor cariporide (10 μM), SGK1‐inhibitors EMD638683 (50 μM) and GSK650349 (10 μM) and ROCK‐inhibitors Y‐27632 (10 μM) and fasudil (100 μM). TAC treatment rapidly and significantly increased cell volume and actin polymerization, effects abolished in the presence of cariporide. Thus, mAR‐activation activates cariporide‐sensitive Na + /H + ‐exchangers, an effect requiring SGK1 and ROCK activity. Abstract : In prostate cancer cells membrane androgen receptor (mAR) activation increases pH. mAR activation upregulates cariporide sensitive Na + /H + exchanger (NHE). The effect of mAR on pH and NHE requires serum & glucocorticoid inducible kinase. The effect of mAR on pH and NHE requires Rho‐associated protein kinase.